Telaah Kritis Terhadap Karakteristik Sastra Arab Masa Jahiliyah dan Islam - Ahmad Bachmid (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2004)
Arabic Literature contains prose and poetry. Aase consists of Masal speeches (Khatabah, Novels, and Essays (Rasail). So the characteristics of pre-Islamic prose lasted until the Islamic period without any changes on their purposes like loving, appreciating, insisting, encouraging, mourning, and apologizing.